Ideological Extremism or Far-Right Attitudes? The Role of Ideology for COVID-19 Scepticism. Issue 4 (2nd October 2022) - Küppers, Anne; Reiser, Marion
ABSTRACT: COVID-19 sceptics view the virus as harmless (i.e., not worse than a casual flu). While political orientation appears to play a crucial role in developing these sceptical positions, previous research showed inconsistent findings on the relationship between COVID-19 related beliefs and ideological orientation: Whereas various studies find close ties between far-right attitudes and COVID-19 related beliefs, other research suggests that sceptical views are linked to extremism on both ends of the ideological spectrum. We contribute to this debate by investigating the underlying ideological foundations of COVID-19 scepticism on a more fine-grained conceptualisation and measurement of ideological orientation and by focusing on a case with a prevalence of support for parties at both ideological fringes. Using data from a representative survey conducted in the East German region of Thuringia in autumn 2020, we show a strong significant link between far-right political attitudes and COVID-19 scepticism, as well as a weaker link between extremism on both sides of the ideological spectrum and scepticism.